A new species of the family Heterolatzeliidae from the Balkan Peninsula (Diplopoda, Chordeumatida) - Antić, Dragan Ž.; Tomić, Vladimir T.; Rađa, Tonći; Lučić, Luka R.; Dudić, Boris D.; Makarov, Slobodan E. (Zootaxa, 2015)
A new species of Heterolatzelia Verhoeff, 1897, H. karlstrasseri sp. n., is described from the Đatlo Cave in east Herzegovina. A brief discussion about the relationship between H. karlstrasseri sp. n. and H. durmitorensis Gulička, 1968 and a distribution map of the family Heterolatzeliidae are presented.